IoT Platforms and Hardware Integrations for Industry 4.0 Applications - Athula Kulatunga, N.; Sampaio, Daniel J. B. S. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2019)
The concept of Industry 4.0 (I4.0) or the 4th Industrial Revolution, formulated in Germany, now spreading through the world, challenges the existing manufacturing industry to adopt new standards to increase productivity and save resources through the Internet of Thing (IoT) platforms. Adaptation of I4.0 has been sluggish due to lack of training and skill. Engineers and technicians need new skills, related hardware and software solutions to transform Industry 3.0 (I3.0) manufacturing facilities to I4.0 facility. Machines in I4.0 factory are cyber-physical systems with capabilities to make their own decisions based on data collected via cloud-based IoT platforms. These platforms consist of data subscribers and publishers and are analyzed through machine learning algorithms. This paper describes available technologies to implement I4.0 in a manufacturing facility, using Energy Management 4.0 as an example. The smart factory must reach a certain maturity related energy management. The technology presented in this paper helps to achieve some maturity level without spending high initial investments. These technologies are also applicable to realize economic savings in other aspects of I4.0.
Keywords: Industry 4.0; Internet of Things